Frequency and Factors of Unmet Need for Family Planning in a Rural Setting of Pakistan: A Cross-Sectional Study - Fatima Tariq; Sana Sarfraz; Areeba Mehreen; Mohi Ud Din; Areej Nisar; Humayun Suqrat Hasan Imam (Journal of the Dow University of Health Sciences)
Objective: The study aimed at identifying the unmet need for family planning and identifying its determinants among married women.